Negative Creativity in Education: Features, Threats and Research Perspectives - Meshkova N.V; Enikolopov S. N. (Moscow State University of Psychology and Education, 2017)
The article discusses the phenomenon of negative creativity in the field of education which results in unintentional harm. Outcomes of psychological studies as well as innovations in education are analysed in two aspects: first, personal influence of creative teachers on students; second, creative resistance of participants of the educational process. The authors developed the Comprehensive Model of Relationship between Creativity and Deviation that helped to reveal the specifics of negative creativity in education which may be crucial for developing standards and regulations as well as for teacher training and selection. These specifics include the following: 1) unintentional negative and delayed impact of creative personality on students; 2) ill-conceived methods of implementing innovations in education which provoke negative creativity as a legitimate way to overcome norms and restrictions in participants of the educational process; 3) contradiction between the legitimacy of the goal and means that leads to discredit and failure of innovations in education. The paper formulates some hypotheses and outlines perspectives of further research of negative creativity in educational environment.